2014
DOI: 10.5811/westjem.22550.9.22550
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Novel Ultrasound Technique for Confirmation of Endotracheal Intubation by Expert and Novice Emergency Physicians

Abstract: IntroductionRecent research has investigated the use of ultrasound (US) for confirming endotracheal tube (ETT) placement with varying techniques, accuracies, and challenges. Our objective was to evaluate the accuracy of a novel, simplified, four-step (4S) technique.MethodsWe conducted a blinded, randomized trial of the 4S technique utilizing an adult human cadaver model. ETT placement was randomized to tracheal or esophageal location. Three US experts and 45 emergency medicine residents (EMR) performed a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 16 publications
(25 reference statements)
2
25
0
Order By: Relevance
“…The airway cast was produced using a negative-pressure chamber that facilitated passive passage of silicone into the airways and avoided airway distension (26). Current use of airway ultrasound is limited to a few indications, such as percutaneous tracheostomy (27) and confirmation of endotracheal position during intubation (28). Our findings extend previous use of tracheal ultrasound in lambs to suggest a role for tracheal ultrasound in the evaluation of tracheomalacia in human newborns (29).…”
Section: Discussionsupporting
confidence: 76%
“…The airway cast was produced using a negative-pressure chamber that facilitated passive passage of silicone into the airways and avoided airway distension (26). Current use of airway ultrasound is limited to a few indications, such as percutaneous tracheostomy (27) and confirmation of endotracheal position during intubation (28). Our findings extend previous use of tracheal ultrasound in lambs to suggest a role for tracheal ultrasound in the evaluation of tracheomalacia in human newborns (29).…”
Section: Discussionsupporting
confidence: 76%
“…We were able to correctly identify this phenomenon once the US transducer was moved to the contralateral side. A novel technique proposed by Gottlieb et al used 4 steps to confirm ETT placement in cadavers. The technique involved scanning each side of the neck until the location of the tube was positively identified via a “tube‐sliding” artifact and achieved sensitivity and specificity of 96% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies on human and cadaveric models evaluated the sensitivity and specificity of US confirmation of tube placement in the trachea. [30][31][32][33][34][35][36][37][38] In a meta-analysis of 969 intubations performed in emergency and elective situations, Das et al showed that transtracheal ultrasonography's pooled sensitivity and specificity were 0.98 (95% CI, 0.97 to 0.99) and 0.98 (95% CI, 0.95 to 0.99), respectively. 11 In emergency scenarios, transtracheal US showed an aggregate sensitivity and specificity of 0.98 (95% CI, 0.97 to 0.99) and 0.94 (95% CI, 0.86 to 0.98), respectively.…”
Section: Confirmation Of Tracheal Intubationmentioning
confidence: 99%